The Effect of Social Capital on the Product Innovativeness and Marketing Performance in Indonesian Furniture Small and Medium-sized Enterprises - Nupus, Hayati; Setiadi, Roby; Soesanto, Harry (International Review of Management and Marketing, 2017)
<!--[if gte mso 9]> Normal 0 false false false IN X-NONE AR-SA <![endif]--> The application of product innovativeness is considered to bring opportunities for product development, technological advances, and the earning of profit for the company. For certain products based on the rapidly changing mass-production technique and design such as small-scale traditional furniture, employees play a key role in generating innovative products. In such context, the relational quality among the employees in the form of social capital is considerably important to analyze the role of trust among internal stakeholders, and its impact on the innovativeness and performance. This study concluded that the internal structural relationship is more likely to improve the innovativeness and performance of furniture SMEs. The novelty of this study lies on its focus on the extent that the innovative product can be produced by emphasizing on the establishment of internal social capital and stakeholder trust without involving external collaboration or network interaction. Keywords: social capital, trust, product innovativeness, performance, furniture SMEs, Indonesia JEL Classifications: J24, M31 <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->